2011
DOI: 10.1016/j.ijsu.2011.07.431
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study examining thrombolysis for occluded femoro-popliteal grafts – Is it worthwhile?

Abstract: CDT can achieve reasonable results in this group of challenging patients and may be seen as a useful accessory in the vascular toolkit. However, precise indications for its use need further clarification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In a study with similar patients, 60% (12/20) of successful CDT cases had an underlying stenotic lesion which required angioplasty. 15 In our study, in the remaining 15 cases, two underwent patch plasty for distal graft anastomosis in addition to surgical thrombectomy; two underwent thrombectomy and distal bypass, three underwent thrombectomy and patch plasty for distal graft anastomosis þ PTA/stenting and eight underwent thrombectomy þ PTA/stenting to achieve graft patency. So, CDT can be an alternative initial therapy instead of surgery, but it should be kept in mind that additional surgical or endovascular procedures are generally required in these patients with acute femoropopliteal graft occlusion.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In a study with similar patients, 60% (12/20) of successful CDT cases had an underlying stenotic lesion which required angioplasty. 15 In our study, in the remaining 15 cases, two underwent patch plasty for distal graft anastomosis in addition to surgical thrombectomy; two underwent thrombectomy and distal bypass, three underwent thrombectomy and patch plasty for distal graft anastomosis þ PTA/stenting and eight underwent thrombectomy þ PTA/stenting to achieve graft patency. So, CDT can be an alternative initial therapy instead of surgery, but it should be kept in mind that additional surgical or endovascular procedures are generally required in these patients with acute femoropopliteal graft occlusion.…”
Section: Discussionmentioning
confidence: 77%
“…In a study with similar patients, 60% (12/20) of successful CDT cases had an underlying stenotic lesion which required angioplasty. 15…”
Section: Discussionmentioning
confidence: 99%
“…Clinical outcomes of CDT for chronic obstructions appeared to be encouraging. It’s reported that several week 13 or month-old 6 femoropopliteal occlusions can be canalized again by CDT with a high success rate. PTA of femoropopliteal arteries seems to have a better prognosis if combined with CDT, especially in longer occlusions.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, CDT was seldom used for chronic femoropopliteal occlusive disease in literatures, except for acute ischemia. [11][12][13][14] This study aims to determine the safety and effectiveness of CDT for patients with chronic femoropopliteal occlusive disease during a 6-year period.…”
Section: Introductionmentioning
confidence: 99%
“…Endovascular devices have improved dramatically in recent years, and the clinical data after EVT for ALI in today's clinical setting have considerably improved 1) . Previous reports demonstrated that the rates of postoperative complications in ALI patients after EVT with catheter-directed thrombolysis ranged from 11% to 30.3% and that the 30-day mortality rates were 8.2% or less [15][16][17][18][19][20][21][22][23][24] . De Athayde Soares et al 25) obtained similar limb salvage and overall survival estimates at 720 days in an open surgery group and EVT group (79.2% vs 90.6% [P 0.27] and 53.0% vs 60.8% [P 0.45], respectively).…”
Section: Advance Publication Journal Of Atherosclerosis and Thrombosismentioning
confidence: 99%